Coping Motives Moderate Efficacy of Personalized Normative Feedback Among Heavy Drinking U.S. College Students - Young, Chelsie M. (J Stud Alcohol Drugs, 2016)
OBJECTIVE: Personalized normative feedback (PNF) interventions have received empirical support, are presumed to work by reducing normative misperceptions, and have been found to be particularly efficacious for those who drink for social reasons. However, PNF interventions also offer direct comparisons between one’s own drinking and normative drinking, which may be especially important for coping drinkers. The present research evaluated whether reduced perceived norms and drinking at follow-ups varied as a function of coping motives. METHOD: Aims were examined as a secondary analysis of a PNF intervention study among 252 U.S. college students. Following baseline assessment, participants were randomly assigned to receive PNF or assessment only. Follow-up assessments occurred 3 and 6 months after baseline. RESULTS: Findings indicated that the PNF intervention was more effective at both follow-ups in reducing drinking, but not alcohol use problems, for participants scoring higher in coping motives. Furthermore, coping motives were the only drinking motive that uniquely moderated PNF efficacy. Analyses indicated that intervention effects on drinking varied as a function of coping drinking motives; however, intervention effects on norms did not vary by coping motives. Finally, coping motives were found to moderate associations between perceived norms and drinking. CONCLUSIONS: These results suggest that coping motives may be useful for identifying young adults—and presumably others—who can most benefit from PNF approaches. Furthermore, PNF may influence future drinking behavior through mechanisms other than changes in perceived norms. Future investigations could examine other pathways through which PNF may reduce drinking.